Spinel magnesium ferrite (MgFe2O4): a glycine-assisted colloidal combustion and its potentiality in gas-sensing application - Nadargi, Digambar; Umar, Ahmad; Nadargi, Jyoti; Patil, Jayvant; Mulla, Imtiaz; Akbar, Sheikh; Suryavanshi, Sharad (Chemosensors, 2022)
Herein, we describe the facile synthesis of spinel MgFe2O4 ferrite and its potential use as a gas sensor using a straightforward and reliable sol-gel approach, i.e., the glycine-assisted auto-combustion route. The novelty in obtaining the sensing material via the auto-combustion route is its inherent simplicity and capability to produce the material at an industry scale. The said cost-effective process makes use of simple metal salts (Mg and Fe-nitrates) and glycine in an aqueous solution, which leads to the formation of spinel MgFe2O4 ferrite. A single-phase crystallinity with crystallite sizes ranging between 36 and 41 nm was observed for the synthesized materials using the X-ray diffraction (XRD) technique. The porous morphologies of the synthesized materials caused by auto-ignition during the combustion process were validated by the microscopic investigations. The EDS analysis confirmed the constituted elements such as Mg, Fe, and O, without any impurity peaks. The gas-sensing ability of the synthesized ferrites was examined to detect various reducing gases such as LPG, ethanol, acetone, and ammonia. The ferrite showed the highest response (>80%) toward LPG with the response and recovery times of 15 s and 23 s, respectively. Though the sensor responded low toward ammonia (similar to 30%), its response and recovery times were very quick, i.e., 7 s and 9 s, respectively. The present investigation revealed that the synthesized ferrite materials are good candidates for fabricating high-performance sensors for reducing gases in real-world applications.
Keywords: Gas sensors; glycine combustion; MgFe2O4; reducing gases